Comparison Between Efficacy of Methylprednisolone and Triamcinolone in Intra Articular Injection for Osteoarthritis Pain Relief (Medical Forum Monthly, 2024)
Objective: To compare the effect of two different corticosteroid regimens methylprednisolone acetate and triamcenolone acetate in bilateral and symmetrical knee osteoarthritis (OA) pain relief.Study Design: A Randomize Control Trial study.Place and Duration of Study: This study was conducted at the Department of Anaesthesia, Intensive care and Pain Management, Hameed Latif Hospital, Lahore from 1st November 2016 to 30th October 2017.Materials and Methods: After getting ethical approval from hospital ethical committee and informed consent from patients to be included in study. Total 100 patients were enrolled in study through non probability consecutive sampling technique, and all patients were divided in two equal groups randomly using lottery method. Data was collected on pre designed Performa. Statistical analysis was done by using SPSS version 24 for all variables, mean and SD presentation for continuous data like age and VAS score, WOMAC score and frequency percentage presentation was given for categorical data like gender. P value <0.05 was considered as significant.Results: Total 100 patients were included, in this study. The mean age and BMI of the patients was 60.33±2.61 years and 27.06±2.42 kg/m2 respectively. A significant decrease in VAS score for both knees (right and left) was observed after intra articular injection bilaterally. Measurements were done at 2, 4, 8, 12 and 24 weeks after injection administration (p<0.005).Conclusion: Results of our study revealed that intra articular injection is an effective mode of treatment when used for the management of osteoarthritis knee pain (p<0.005). When we compared two steroid regimens Methylprednisolone and Triamcenolone it was observed that there is no significant difference among both groups, both are equally effective.